Directive Illocutionary Act Used by The Main Character in “The End of the F***ing World” - Prabawa, I Dewa Gede Bagus; Andri Permana, I Putu (Humanis, 2024)
The purpose of this study is to analyzedirective illocutionary act, spesifically about how action can occur only with the use of language spoken by the main characters  in The End of the F***ing World series.Theory by Halliday and Hasan (1985) was applied to analyse the situational context which refers to the place, topic of the conversation, participants’s relationship, and how language is used in the conversation. There is also theory by Yule (1996) about the explanation of action that performed just by utterance called directive illocutionary act and divided into command, order, request and suggestion. This study used a descriptive qualitative method... The results found all types of directive illocutionary act used by the main characters in their daily life to make someone do something, where the success rate in using directive illocutionary act is related with the situational context.. This study used formal and informal methods in its presentation.